2015
DOI: 10.1007/s10942-015-0227-6
|View full text |Cite
|
Sign up to set email alerts
|

Is Trait Rumination Associated with the Ability to Generate Effective Problem Solving Strategies? Utilizing Two Versions of the Means-Ends Problem-Solving Test

Abstract: This study examined the relationship between trait rumination and the effectiveness of problem solving strategies as assessed by the Means-Ends Problem-Solving Test (MEPS) in a nonclinical population. The present study extended previous studies in terms of using two instructions in the MEPS: the second-person, actual strategy instructions, which has been utilized in previous studies on rumination, and the third-person, ideal-strategy instructions, which is considered more suitable for assessing the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
(91 reference statements)
1
17
0
Order By: Relevance
“…To estimate the stable predictive powers of each variable, linear mixed models were analyzed in which depression, rumination (assessed with the RRS total scale), and each dimension of social problem solving were treated as fixed factors, with the same scale or subscale assessed at the next time point as dependent variables (details and advantages of this analytic method are described in the Statistical Analysis section). Because previous cross-sectional studies indicated that rumination, negative problem orientation, and avoidance style are associated with one another (McMurrich and Johnson 2008 ; Hasegawa et al 2015b , 2016 ), we predicted that these variables would also show longitudinal associations. Moreover, considering the observed very weak or absent correlations between impulsivity/carelessness style and rumination (Hasegawa et al 2015b , 2016 ), we expected that impulsivity/carelessness style would not be predicted by rumination, and vice versa.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…To estimate the stable predictive powers of each variable, linear mixed models were analyzed in which depression, rumination (assessed with the RRS total scale), and each dimension of social problem solving were treated as fixed factors, with the same scale or subscale assessed at the next time point as dependent variables (details and advantages of this analytic method are described in the Statistical Analysis section). Because previous cross-sectional studies indicated that rumination, negative problem orientation, and avoidance style are associated with one another (McMurrich and Johnson 2008 ; Hasegawa et al 2015b , 2016 ), we predicted that these variables would also show longitudinal associations. Moreover, considering the observed very weak or absent correlations between impulsivity/carelessness style and rumination (Hasegawa et al 2015b , 2016 ), we expected that impulsivity/carelessness style would not be predicted by rumination, and vice versa.…”
Section: Introductionmentioning
confidence: 98%
“…Because previous cross-sectional studies indicated that rumination, negative problem orientation, and avoidance style are associated with one another (McMurrich and Johnson 2008 ; Hasegawa et al 2015b , 2016 ), we predicted that these variables would also show longitudinal associations. Moreover, considering the observed very weak or absent correlations between impulsivity/carelessness style and rumination (Hasegawa et al 2015b , 2016 ), we expected that impulsivity/carelessness style would not be predicted by rumination, and vice versa. Given the findings of previous research (Nolen-Hoeksema and Morrow 1991 ; Nolen-Hoeksema 2000 ; Spasojević and Alloy 2001 ; Anderson et al 2011 ; Hasegawa et al 2015a ), we predicted that rumination, negative problem orientation, and impulsivity/carelessness style would predict increased depressive symptoms assessed 4 weeks later, even after controlling for initial depression levels.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Rumination is a mode of responding to distress or depressed mood that entails perseverative thinking about one's problems or emotions (Nolen-Hoeksema, 1991;Nolen-Hoeksema et al, 2008). While rumination may give individuals the impression that they are solving their problems (Papageorgiou & Wells, 2001), rumination impairs problem solving and is associated with the endorsement of more negative cognitions , negatively biased interpretations of hypothetical scenarios, and the generation of less effective solutions to problems (Hasegawa et al, 2016), especially for individuals in dysphoric states , Lyubomirsky & Nolen-Hoeksema, 1995. Evidence that rumination is a maladaptive response to negative mood comes from studies indicating that rumination is a less effective approach to down-regulating negative emotions in daily life in comparison to other emotion regulation strategies (Lennarz et al, 2018), that engaging in rumination when distressed is associated with a greater likelihood of experiencing future depressive episodes (Just & Alloy, 1997), and that rumination mediates the association between depressed mood and poor self-reported health (Slavish & Graham-Engeland, 2015).…”
Section: Introductionmentioning
confidence: 99%